2015
DOI: 10.1120/jacmp.v16i1.5069
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the monoisocentric and dual isocentric techniques in chest wall radiotherapy of mastectomy patients

Abstract: The monoisocentric (MIT) and dual isocentric (DIT) techniques are compared for the mastectomy patients undergoing chest wall radiotherapy, and a new practical method is suggested for determining the dose calculation reference point to be used in the MIT. Data of 18 mastectomy patients having chest wall radiotherapy were used. To find the appropriate dose calculation reference point for the MIT, the target tissue was divided into nine regions with 17 points as the appropriate candidates. After finding the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…A similar expectation existed regarding hot and cold points (points with higher and lower doses than the prescribed dose) in field junction regions of DIT, which was also confirmed by previous researches. 18,23 As expected, it was confirmed that D max in the field junction and overlap regions for DIT was significantly higher compared with MIT (59•59 versus 52•8 Gy in 3D-CRT and 56•48 versus 51•6 Gy in IMRT). Previous investigations have also reported similar findings in this regard.…”
supporting
confidence: 67%
See 4 more Smart Citations
“…A similar expectation existed regarding hot and cold points (points with higher and lower doses than the prescribed dose) in field junction regions of DIT, which was also confirmed by previous researches. 18,23 As expected, it was confirmed that D max in the field junction and overlap regions for DIT was significantly higher compared with MIT (59•59 versus 52•8 Gy in 3D-CRT and 56•48 versus 51•6 Gy in IMRT). Previous investigations have also reported similar findings in this regard.…”
supporting
confidence: 67%
“…Assaoui et al 18 and Banaei et al 23 reported the same results for dosimetric parameters regarding the chest wall, lung and heart resulting from MIT and DIT with 3D-CRT technique. In another study by Lefkopoulos et al, 32 a general optimisation procedure for stereotactic small-beam using multi-isocentric radiotherapy was investigated.…”
mentioning
confidence: 56%
See 3 more Smart Citations